Gelombang Kedua Gerakan Feminisme di Indonesia (1982-1998) - Astri Aristiani; Abdul Syukur; Umasih (PERIODE: Jurnal Sejarah dan Pendidikan Sejarah, 2021)
The New Order government created its own gender politics. They adopted the concept of "Motherism" and viewed women as mothers and wives. The life of the independent feminism movement in the period 1982-1998 had to experience cat-and-cat with the New Order government, so it is not uncommon for some of these organizations to be illegal. In the midst of repressive government attitudes, the independent feminism movement is challenged. But it was able to go through with a mature strategy, so that many of them were able to survive until the New Order was dethroned, even able to cooperate with the international feminism movement. Then at the time of the May 1998 riots, independent feminism movements either at the center orpu areas synergized with each other to voice freedom. This study aims to examine the dynamics of life of the second wave of feminism movement in Indonesia in 1982-1998. This study uses historical methods whose data is obtained from interviews, literature studies and presented descriptively-narratively. Pemerintah Orde Baru menciptakan politik gender tersendiri. Mereka mengadopsi konsep “Ibuisme” dan memandang perempuan sebagai ibu dan istri. Kehidupan gerakan feminisme independen pada periode 1982-1998 harus mengalami kucing-kucingan dengan pemerintah Orde Baru, sehingga tidak jarang dari beberapa organisasi ini bersifat ilegal. Di tengah sikap pemerintah yang represif, gerakan feminisme independen banyak mendapat tantangan. Namun hal tersebut mampu dilalui dengan strategi yang matang, sehingga banyak dari mereka yang mampu bertahan hingga Orde Baru lengser, bahkan bisa menjalin kerjasama dengan gerakan feminisme internasional. Kemudian pada saat kerusuhan Mei 1998, gerakan feminisme independen baik yang berada di pusat ataupu daerah saling bersinergi untuk menyuarakan kebebasan. Penelitian ini bertujuan untuk mengkaji mengenai dinamika kehidupan gelombang kedua gerakan feminisme di Indonesia pada tahun 1982-1998. Penelitian ini menggunakan metode historis yang datanya didapat dari hasil wawancara, kajian kepustakaan dan disajikan secara deskriptif-naratif.